Impact of Obesity on Warfarin Reversal With Fixed-Dose Factor VIII Inhibitor Bypassing Activity (aPCC). Issue 7 (July 2021) - McKinney, Amanda L.; Dailey, Lindsey M.; McMillen, James C.; Rowe, A. Shaun
Background: Data are limited addressing anticoagulant reversal in obese patients using activated prothrombin complex concentrate (aPCC). Objective: Assess the impact of obesity on INR reversal with fixed aPCC dosing. Methods: Institutional review board–approved, retrospective cohort conducted in a large academic medical center. Patients 18 years or older who received fixed-dose aPCC for warfarin-associated hemorrhage were included. Patients who received aPCC for any other indications or who had no follow-up INR after aPCC administration were excluded. Patients with an INR of 5 or greater received 1000 units aPCC, whereas those with INR less than 5 received 500 units aPCC, per institutional protocol. Patients were stratified into obese and nonobese based on body mass index. Primary end point was INR reversal, defined as repeat INR of 1.4 or less within 4 hours following aPCC treatment, without a repeated dose. Secondary end points included percentage change in INR, proportion of patients requiring an additional dose of aPCC, bleeding complications, thrombotic complications, hospital length of stay, and in-hospital mortality. Results: 259 patients were included, of whom 83 were obese (32%). A significantly higher proportion of nonobese patients achieved an INR of 1.4 or less within 4 hours of treatment (169 [96.02%] vs 69 [83.13%]; P = 0.0004). There were no differences in any secondary end points. Conclusion and Relevance: When fixed-dose aPCC is used for warfarin reversal, obesity is associated with a significantly lower rate of INR reversal, without increased bleeding. This study adds to the limited amount of literature on aPCC dosing in obesity.